Long-term effects of air pollution on the incidence and progression of multiple sclerosis: A population cohort study in Isfahan, Iran - Omid Mirmosayyeb; Saeed Vaheb; Alireza Afshari-Safavi; Aysa Shaygannejad; Mohammad Ali Sahraian; Ali Atamaleki; Sharareh Eskandarieh; Vahid Shaygannejad (PLoS ONE, 2025)
Background Multiple sclerosis (MS) is a neurodegenerative disorder of the central nervous system characterized by autoimmune inflammation. Recent research indicates that environmental factors, particularly air pollution, may significantly affect the risk of developing MS. Objective This study investigates the association between PM2.5 levels, as a measure of air pollution, and the incidence of MS in Isfahan, Iran, a city with one of the highest reported MS prevalence rates in the country. Methods A retrospective population-based cohort study was conducted using data from the National MS registry of Iran and Isfahan’s air pollution monitoring department from 2011 to 2021. The incidence of MS across urban areas was calculated, and the relationship between PM2.5 levels and the incidence rate ratio (IRR) of MS was assessed using a Poisson generalized regression models. Results PM2.5 levels averaged 41.99 µg/m3 across the study period (first year: 59.21 ± 33.56; mid-study: 30.51 ± 11.77; final year: 37.71 ± 53.64), persistently exceeding safety standards. Three-year cumulative exposure showed significant association with higher MS incidence (IRR = 1.027, 95%CI = 1.022–1.031, p < 0.001) and correlated with disease progression in progressive MS cases. Conclusion Long-term exposure to PM2.5 is associated with an increased incidence of MS and disease progression, emphasizing the critical need for improved air quality management strategies.